Enhanced trophic transfer of chlorpyrifos from resistant Hyalella azteca to inland silversides (Menidia beryllina) and effects on acetylcholinesterase activity and swimming performance at varying temperatures. (15th December 2021) - Fuller, Neil; Huff Hartz, Kara E.; Johanif, Nadhirah; Magnuson, Jason T.; Robinson, Eleni K.; Fulton, Corie A.; Poynton, Helen C.; Connon, Richard E.; Lydy, Michael J.
Abstract: Chlorpyrifos, an organophosphate (OP) insecticide, is prevalent in aquatic systems globally and is often implicated in aquatic toxicity during storm events. Chlorpyrifos induces toxicity by inhibition of acetylcholinesterase (AChE) activity, which has been related to alterations to fish swimming performance. Resistance to organophosphate insecticides, including chlorpyrifos, is prevalent in populations of the epibenthic amphipod Hyalella azteca in areas with known OP exposure. Previous studies have demonstrated an elevated bioaccumulation potential of insecticide-resistant prey items, however the potential for trophic transfer of chlorpyrifos from OP-resistant prey items and associated neurotoxic effects in fish predators has not been studied. Consequently, the present study aimed to determine the potential for trophic transfer of chlorpyrifos from OP-resistant H. azteca to a known predator, the inland silverside, Menidia beryllina at two temperatures (18 and 23 °C) to simulate temperature changes associated with global climate change (GCC). Fish were fed either 14 C-chlorpyrifos-dosed H. azteca or control animals for 7 d, after which total bioaccumulation, percent parent chlorpyrifos, brain AChE activity and swimming performance (ramp-Ucrit ) were determined. Fish fed chlorpyrifos-dosed H. azteca bioaccumulated chlorpyrifos ranging from 29.9 to 1250 ng/g lipid, demonstrating the potential for trophic transfer. Lower bioaccumulation and greater biotransformation were observed in M. beryllina at 23 °C as compared to 18 °C, though this was not statistically significant. A significant 36.5% reduction in brain AChE activity was observed in fish fed chlorpyrifos-dosed H. azteca at 23 °C only, which may be attributed to increased biotransformation of parent chlorpyrifos to more potent AChE-inhibiting metabolites. Dietary chlorpyrifos exposure had no significant effect on swimming performance in M. beryllina, though ramp-Ucrit was significantly increased by 25% at 23 as compared to 18 °C. These findings confirm the potential for trophic transfer of chlorpyrifos from OP-resistant prey to fish predators and the potential for elevated temperatures to exacerbate the neurotoxic effects of chlorpyrifos.